Pharmacokinetics and Biodistribution of Thymoquinone-loaded Nanostructured Lipid Carrier After Oral and Intravenous Administration into Rats - Zakarial Ansar FH (Dove Medical Press, 2020)
Fatin Hannani Zakarial Ansar,1 Saiful Yazan Latifah,1,2 Wan Hamirul Bahrin Wan Kamal,3 Khei Choong Khong,3 Yen Ng,3 Jia Ning Foong,1 Banulata Gopalsamy,2 Wei Keat Ng,1 Chee Wun How,4 Yong Sze Ong,1 Rasedee Abdullah,2,5 Mohd Yusmaidie Aziz6 1Laboratory of Molecular Medicine, Institute of Bioscience, Universiti Putra Malaysia, Serdang, Selangor, Malaysia; 2Department of Biomedical Science, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Serdang, Selangor, Malaysia; 3Laboratory of Preclinical Study, Block 24, Medical Technology Division, Malaysian Nuclear Agency, Kajang, Selangor, Malaysia; 4Laboratory of Vaccines and Immunotherapeutics, Institute of Bioscience, Universiti Putra Malaysia, Serdang, Selangor, Malaysia; 5Department of Veterinary Pathology and Microbiology, Faculty of Veterinary Medicine, Universiti Putra Malaysia, Serdang, Selangor, Malaysia; 6Advanced Medical and Dental Institute, University of Science Malaysia, Kepala Batas, Pulau Pinang, MalaysiaCorrespondence: Saiful Yazan Latifah; Wan Hamirul Bahrin Wan Kamal Tel +60 3 89472308Fax +60 3 89436178Email latifahsy@upm.edu.my; mirul@nuclearmalaysia.gov.myBackground: Thymoquinone (TQ), an active compound isolated from Nigella sativa, has been proven to exhibit various biological properties such as antioxidant. Although oral delivery of TQ is valuable, it is limited by poor oral bioavailability and low solubility. Recently, TQ-loaded nanostructured lipid carrier (TQ-NLC) was formulated with the aim of overcoming the limitations. TQ-NLC was successfully synthesized by the high-pressure homogenization method with remarkable physiochemical properties whereby the particle size is less than 100 nm, improved encapsulation efficiency and is stable up to 24 months of storage. Nevertheless, the pharmacokinetics and biodistribution of TQ-NLC have not been studied. This study determined the bioavailability of oral and intravenous administration of thymoquinone-loaded nanostructured lipid carrier (TQ-NLC) in rats and its distribution to organs.Materials and Methods: TQ-NLC was radiolabeled with technetium-99m before the administration to the rats. The biodistribution and pharmacokinetics parameters were then evaluated at various time points. The rats were imaged at time intervals and the percentage of the injected dose/gram (%ID/g) in blood and each organ was analyzed.Results: Oral administration of TQ-NLC exhibited greater relative bioavailability compared to intravenous administration. It is postulated that the movement of TQ-NLC through the intestinal lymphatic system bypasses the first metabolism and therefore enhances the relative bioavailability. However, oral administration has a slower absorption rate compared to intravenous administration where the AUC0-∞ was 4.539 times lower than the latter.Conclusion: TQ-NLC had better absorption when administered intravenously compared to oral administration. However, oral administration showed greater bioavailability compared to the intravenous route. This study provides the pharmacokinetics and biodistribution profile of TQ-NLC in vivo which is useful to assist researchers in clinical use.Keywords: thymoquinone, nanostructured lipid carrier, bioavailability, biodistribution, pharmacokinetics